OP0296 Hypoxia-Inducible Factor 2A Regulates Macrophage Function in Rheumatoid Arthritis. (10th June 2014) - Hardy, W.; Wright, F.; Hawtree, S.; Fearon, U.; Veale, D.; Perretti, M.; Wilson, A.; Muthana, M.
Abstract : Background: In rheumatoid arthritis (RA), the influx of inflammatory cells as well as the aggressive proliferation of fibroblast-like synovial cells (FLS) outstrips the oxygen supply from blood vessels leading to joint hypoxia. Macrophages accumulate in these hypoxic sites where they possess broad pro-inflammatory, destructive and remodelling potential leading to inflammation and joint destruction. Macrophages respond to such hypoxia by up regulating the hypoxia inducible transcription factors – HIF-1a and -2a, which leads to the up-regulation of genes involved in proliferation, angiogenesis, and glucose metabolism. Objectives: To characterise the HIF-2a expressing macrophage populations in response to joint hypoxia, and in particular to dissect out the effects of HIF-2 in a murine model of arthritis. Methods: Tissue from RA patients was assessed for oxygen levels using an oxygen/temperature probe then sections were immunostained with anti-HIF-2a and co-localised with the pan-macrophage markers CD68 as well as other M1 and M2 macrophage markers. Cell-specific RNA was purified from CD68+ macrophages in RA tissue by laser capture microdissection and differential gene expression was determined using the RT 2 Profiler PCR inflammatory arrays. The significance of HIF-2a was also evaluated in the K/BxN serum transfer model in mice bearing a targeted deletion of HIF-2a in myeloid cells including macrophages (HIF2fl/fl; LysM-Cre+' mice). Arthritis was assessed clinically and histologically. Results: In patients with severely hypoxic tissue (pO2 <20 mmHg), CD68+ macrophages predominately expressed HIF-2a compared to macrophages from mildly hypoxic (pO2 >20 mmHg) tissue (58%±10.2 vs. 15±9.3 p =0.01, respectively). This reduced in vivo oxygen tension (pO2 <20 mmHg) also positively correlated with macrophages expressing GLUT 1 and receptors for VEGF (Flt1), angiopoietin "Tie2" and mannose "CD206", all markers associated with M2-skewed macrophages. In addition, these hypoxic macrophages expressed increased mRNA for CXCL-2, -4, -5, IL-1a, IL-6, IL-8 & TNFa compared to macrophages from mildly hypoxic joints. In vivo, macrophages lacking HIF-2a significantly suppressed disease development indicating an indispensable role for HIF-2 in supporting macrophages in K/BxN serum-transfer arthritis. Conclusions: HIF-2a expressing macrophages have an M2-like phenotype in patients with severely hypoxic joints and loss of HIF-2a in macrophages suppressed arthritis in mice. Collectively, our data identify HIF-2a as an important regulator of macrophage function, suggesting it may be a useful therapeutic target for treating RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4257